2003
DOI: 10.1074/jbc.m306503200
|View full text |Cite
|
Sign up to set email alerts
|

Upstream Signaling Pathways Leading to the Activation of Double-stranded RNA-dependent Serine/Threonine Protein Kinase in β-Amyloid Peptide Neurotoxicity

Abstract: One of the hallmarks of Alzheimer's disease is extracellular accumulation of senile plaques composed primarily of aggregated ␤-amyloid (A␤) peptide. Treatment of cultured neurons with A␤ peptide induces neuronal death in which apoptosis is suggested to be one of the mechanisms. We have demonstrated previously that A␤ peptide induces activation of double-stranded RNA-dependent serine/threonine protein kinase (PKR) and phosphorylation of eukaryotic initiation factor 2␣ (eIF2␣) in neurons in vitro. Degenerating n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
83
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 91 publications
(87 citation statements)
references
References 70 publications
4
83
0
Order By: Relevance
“…Ab has been reported to phosphorylate eIF-2a via PKR activation in neuronal cells (Chang et al, 2002b;Suen et al, 2003). We found that minocycline reduced PKR phosphorylation at threonine 446 and 451 induced by Ab 1-42 treatment (Figure 1d).…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Ab has been reported to phosphorylate eIF-2a via PKR activation in neuronal cells (Chang et al, 2002b;Suen et al, 2003). We found that minocycline reduced PKR phosphorylation at threonine 446 and 451 induced by Ab 1-42 treatment (Figure 1d).…”
Section: Discussionmentioning
confidence: 56%
“…PKR is known to play a crucial role in mediating Ab-induced neuronal death because primary cortical neurons from PKR KO mice and neuroblastoma SH-SY5Y cells stably transfected with dominant-negative PKR mutants are less susceptible to Ab toxicity (Chang et al, 2002b). Activated PKR can phosphorylate eIF2a at serine 51 (Suen et al, 2003). Phosphorylation of eIF2a that could increase owing to many factors by Ab 1-42 , APP-CTs expression or Swedish APP transgenes in Tg2576 mice, might contribute to impairment in synaptic plasticity and cognitive function before causing neurodegeneration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism for activation of caspase-3/-8 is not known, but activation of caspase-3 has been suggested to be triggered by Ca 2+ release from the endoplasmic reticulum (ER) [23]. An increase in Ca 2+ concentration has also been reported to lead to activation of caspase-3 [24], while depletion of ER Ca 2+ stores has also been shown to activate PKR and induce phosphorylation of eIF2 [25].…”
Section: +mentioning
confidence: 99%
“…Activation of NF-kB in the muscle of mice has been shown to lead to atrophy through increased expression of proteasome subunits and the E3 ligase, MURF1 (Cai et al, 2004). It occurs through activation of caspases-3 and -8, and the subsequent autophosphorylation of the dsRNA-dependent protein kinase (PKR) (Suen et al, 2003). Autophosphorylation of PKR in skeletal muscle has been shown to inhibit protein synthesis owing to phosphorylation of eukaryotic initiation factor-2 (eIF2) on the a-subunit, and increased protein degradation through the NF-kBmediated induction of the ubiquitin -proteasome pathway (Eley and Tisdale, 2007).…”
Section: Discussionmentioning
confidence: 99%